Analyzing Users’ Trust for Online Health Rumors - Chua, Alton Yeow Kuan (2016)
This paper analyzes users’ trust for online health rumors as a function of two factors: length and presence of image. Additionally, two types of rumors are studied: pipe-dream rumors that offer hope, and bogie rumors that instil fear. A total of 102 participants took part in a 2 (length: short or long) x 2 (presence of image: absent or present) x 2 (type: pipe-dream or bogie) within-participants experiment. A repeated-measures analysis of variance suggest that pipe-dream rumors are trusted when they are short and do not contain images whereas bogie rumors are trusted when they are long and contain images.